Penerapan Crossword Puzzle untuk Meningkatkan Pemahaman Konsep Uang pada Siswa Sekolah Dasar - Latifah Nur Afifah; Rukayah Rukayah; Fadhil Purnama Adi (Universitas Sebelas Maret, 2019)
The purpose of this research was to improve comprehension concept of money at thethird grade students of SD N Kemasan 1 Boyolali by crossword puzzle. The type of thisresearch is classroom action research held in two cycles. The subject of this research wereteacher and 21 students at the third grade of SD N 1 Kemasan academic year 2017/2018. Thedata were collected by interview, observation, test, and document analysis. Data validity istested by content validity, triangulation of source and technique. The data analysis useddescriptive comparative technique and interactive analysis model Miles Huberman. The resultsof research is by applied crossword puzzle can improve comprehension consept of money.